Prevention and control measures significantly curbed the SARS-CoV-2 and influenza epidemics in China - Xiangsha Kong; Feng Liu; Haibo Wang; Ruifeng Yang; Dongbo Chen; Xiaoxiao Wang; Fengmin Lu; Huiying Rao; Hongsong Chen (Elsevier, 2021)
At the end of 2019, an outbreak of pneumonia took place caused by a new coronavirus (SARS-CoV-2 virus), named coronavirus disease 2019 (COVID-19). A series of strict prevention and control measures were then implemented to reduce the spread of the epidemic. Influenza, another respiratory tract virus, may also respond to these measures. To assess the impact of these measures, we used the total number of passengers movement in mainland China from 2018 to 2020 and daily number of railway passenger flow during the 2020 Spring Festival travel rush to reflect the population movement and to analyze newly and cumulatively confirmed COVID-19 and influenza cases. We found that implementing the series of measures against COVID-19 mitigated both COVID-19 and influenza epidemics in China. Prevention and control measures for COVID-19 might be used to control respiratory tract infections to reduce the national health economic burden caused by these pathogens.